2015
DOI: 10.1590/0074-02760150175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the nicotinamide mononucleotide adenylyltransferase of Trypanosoma cruzi

Abstract: The intracellular parasite Trypanosoma cruzi is the aetiological agent of Chagas disease, a public health concern with an increasing incidence rate. This increase is due, among other reasons, to the parasite's drug resistance mechanisms, which require nicotinamide adenine dinucleotide (NAD+). Furthermore, this molecule is involved in metabolic and intracellular signalling processes necessary for the survival of T. cruzi throughout its life cycle. NAD+ biosynthesis is performed by de novo and salvage pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“… 14 , 15 In the context of eukaryotic parasites, our research group has identified and characterised NMNATs from Leishmania braziliensis (LbNMNAT) 16 , Giardia lamblia (GlNMNAT) 17 , and Trypanosoma cruzi (TcNMNAT). 18 Concerning the NMNAT from Plasmodium falciparum (PfNMNAT), different functional and structural aspects have been studied. 19 , 20 However, its quaternary structure has not yet been determined.…”
mentioning
confidence: 99%
“… 14 , 15 In the context of eukaryotic parasites, our research group has identified and characterised NMNATs from Leishmania braziliensis (LbNMNAT) 16 , Giardia lamblia (GlNMNAT) 17 , and Trypanosoma cruzi (TcNMNAT). 18 Concerning the NMNAT from Plasmodium falciparum (PfNMNAT), different functional and structural aspects have been studied. 19 , 20 However, its quaternary structure has not yet been determined.…”
mentioning
confidence: 99%
“…The purification was monitored by SDS-PAGE as described previously (Niño et al 2015). On the other hand, the inclusion body was solubilised using reported protocols (Sambrook & Rusell 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) amplification was performed using the plasmid TcNMNAT-pET100, which has been previously described previously (Niño et al 2015), as the template. The primers used contained a restriction site for BamHI in the 5′ end (5′-CGG GAT CCC GAT GAG CGA TGA CAC AT-3′) and a restriction site for EcoRI in the 3′ end (5′-CCG GAA TTC CGG TCA ACA ATT TTG AGT ATT-3′).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme has been identified in extracellular organisms as Giardia duodenalis that possesses 2 isozymes ( Gd NMNAT1-2) ( Forero-Baena et al., 2015 ) and Saccharomyces cerevisiae which has 3 isozymes ( Sc NMNAT1-3) ( Emanuelli et al., 1999 , 2002 ; Kato and Lin, 2014 ); in Homo sapiens 3 isozymes ( Hs NMNAT1-3) located in the nucleus, the Golgi apparatus and the mitochondria have been reported ( Berger et al., 2005 ). Interestingly, a unique isoenzyme has been identified in intracellular parasites such as Leishmania braziliensis ( Lb NMNAT) ( Contreras et al., 2015 ), Tripanosoma cruzi ( Tc NMNAT) ( Niño et al., 2015 ) and Plasmodium falciparum ( Pf NMNAT) located in the cytoplasm ( O'Hara et al., 2014 ). In these pathogens, the NAD transport mechanisms remain unanalyzed.…”
Section: Introductionmentioning
confidence: 99%